1990
DOI: 10.1080/1120009x.1990.11739013
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Tissue Distribution of Amoxicillin plus Clavulanic Acid after Oral Administration in Man

Abstract: Augmentin (875 amoxicillin and 125 mg potassium clavulanate) was administered orally to patients with chronic bronchitis. Concentrations of amoxicillin and clavulanic acid were measured in serum, sputum and urine. Peak serum levels for amoxicillin of 11.23 +/- 2.61 micrograms/ml were observed at 2 hours and for clavulanic acid of 2.55 +/- 0.54 micrograms/ml at 1 hour. After 9 hours, 50% of the amoxicillin and 39% of the clavulanic acid had been renally excreted. The peak sputum concentration of amoxicillin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Serum amoxicillin concentration found in this study is comparable to levels previously reported [18][19][20][21]; however, what is remarkable here is the high prevalence of children with low plasma levels. Although delays in collecting blood samples cannot be excluded, we ascribe it to a low compliance of the patient to the chemoprophylaxis protocol (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Serum amoxicillin concentration found in this study is comparable to levels previously reported [18][19][20][21]; however, what is remarkable here is the high prevalence of children with low plasma levels. Although delays in collecting blood samples cannot be excluded, we ascribe it to a low compliance of the patient to the chemoprophylaxis protocol (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Department of ''Amedeo Avogadro'' University of Eastern Piedmont in Novara for elective tonsillectomy. All tonsils were removed by cold dissection tonsillectomy, with a mean surgery time of 20 min (range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Previously, patients were treated with 3 doses of amoxicillinclavulanic acid given orally the day before plus a further dose given 2 h before admittance into the operating theatre.…”
Section: Subjects and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…against strain 2, between cefditoren and all other regimens against strains 3 and 4, and between cefuroxime versus both amoxicillin/clavulanic acid regimens against strain 3. Table 2 shows T 1 MIC and log 10 reductions at selected timepoints (8,12 and 24 h), together with the maximal reduction obtained. Bactericidal activity ( 6 3 log 10 reduction) at 12 and 24 h was obtained against all strains with cefditoren, against strains 1 and 2 with cefuroxime and amoxicillin/clavulanic acid t.i.d., but only against strain 1 with amoxicillin/clavulanic acid b.i.d.. Bactericidal activity at 24 h was obtained when T 1 MIC was 1 30% of the dosing interval, a reduction of 1.7-2.0 log 10 was obtained with T 1 MIC of 20-30%, and !…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] were simulated over 24 h. The target total drug pharmacokinetic parameters, based on mean values reported in humans, were as follows: C max = 4.20 g/ml, T max = 2.75 h, and t 1/2 = 1.55 h for cefditoren [6,7] , and C max = 7.70 g/ml, T max = 3.0 h, and t 1/2 = 1.10 h for cefuroxime [8] . For the amoxicillin/clavulanic acid combinations, the half-life and T max of clavulanic acid were employed: T max = 1.0 h, and t 1/2 = 1.1 h [10,11] ; the target C max for amoxicillin was 10.30 g/ml [10,12,13] and for clavulanic acid 2.40 g/ml [10,11] .…”
Section: Kinetic Simulationsmentioning
confidence: 99%